Cancer incidence and mortality patterns in Europe: Estimates for 40 countries and 25 major cancers in 2018. (November 2018) - Ferlay, J.; Colombet, M.; Soerjomataram, I.; Dyba, T.; Randi, G.; Bettio, M.; Gavin, A.; Visser, O.; Bray, F.
Abstract: Introduction: Europe contains 9% of the world population but has a 25% share of the global cancer burden. Up-to-date cancer statistics in Europe are key to cancer planning. Cancer incidence and mortality estimates for 25 major cancers are presented for the 40 countries in the four United Nations-defined areas of Europe and for Europe and the European Union (EU-28) for 2018. Methods: Estimates of national incidence and mortality rates for 2018 were based on statistical models applied to the most recently published data, with predictions obtained from recent trends, where possible. The estimated rates in 2018 were applied to the 2018 population estimates to obtain the estimated numbers of new cancer cases and deaths in Europe in 2018. Results: There were an estimated 3.91 million new cases of cancer (excluding non-melanoma skin cancer) and 1.93 million deaths from cancer in Europe in 2018. The most common cancer sites were cancers of the female breast (523, 000 cases), followed by colorectal (500, 000), lung (470, 000) and prostate cancer (450, 000). These four cancers represent half of the overall burden of cancer in Europe. The most common causes of death from cancer were cancers of the lung (388, 000 deaths), colorectal (243, 000), breast (138, 000) and pancreatic cancer (128, 000). In the EU-28, the estimated number of new cases of cancer was approximately 1.6 million in males and 1.4 million in females, with 790, 000 men and 620, 000 women dying from the disease in the same year. Conclusion: The present estimates of the cancer burden in Europe alongside a description of the profiles of common cancers at the national and regional level provide a basis for establishing priorities for cancer control actions across Europe. The estimates presented here are based on the recorded data from 145 population-based cancer registries in Europe. Their long established role in planning and evaluating national cancer plans on the continent should not be undervalued. Highlights: There were an estimated 3.9 million new cases of cancer and 1.9 million deaths from cancer in Europe in 2018. The most common cancer sites were cancers of the female breast, followed by colorectal, lung and prostate cancer. The most common causes of death from cancer were cancers of the lung, colorectal, breast and pancreatic cancer. These estimates of the cancer burden in Europe provide a basis for establishing priorities for cancer control actions across Europe.